Visitors' understanding of a film and cultural site, and reflections on contemporary China. (October 2021) - Zhang, Xiaoyu (Nancy); Ryan, Chris; Fu, Sicheng (Jasper); Chen, Weijia (Bella)
Abstract: Daguanyuan is used to assess to whether an attraction based on an eighteenth century novel ( Honglou meng ) is still seen as an attractive destination by Chinese visitors. The study is based on a content analysis of interviews of 36 visitors to the tourist/film site. The analysis is supported by the use of text-analysis software. The findings indicate that the site remains attractive but in the case of the majority familiarity with the original story is based on summary texts prepared for schools that reduce the difficulty of the original plot, and two television series. Evidence was found for Guo's Marxist analysis of the storyline aiding dissemination of the novel. The "melodramatic imagination" that informs evaluations of the site commences from recall of the novel's characters, but leads to observations on contemporary China. Nonetheless visitors appreciated the location as providing an insight into the original novel and its times. Highlights: Analyses motives, perceptions and evaluations of Chinese film site The analysis is based on detailed interviews based on five themes with 35 respondents. Use of textual analysis software is reported that confirmed initial thematic analysis. Commentaries on meanings for contemporary China reflect CCP emphasis using Marxist analogies.